Collision test (Thomson Delmar Learning, 2007)
This updated third edition has been completely updated to provide the most current ASE test preparation material for collision repair and refinishing available anywhere. Test B4: Structural Analysis and Damage Repair provides valuable preparation for automotive technicians seeking certification in one or more of the ASE collision repair areas. Readers are afforded scores of opportunities to ascertain their knowledge of critical concepts, through the extensive array of sample problems, ASE-style exams, and competency-specific test questions required for certification by ASE. Refresher materials, helpful test-taking strategies, and thorough explanations round out this comprehensive preparation package.